Haemodialysis for paediatric acute kidney injury in a low resource setting: experience from a tertiary hospital in South West Nigeria (2016)
Background: Acute kidney injury (AKI) is an important cause of preventable mortality among children. Management of AKI may require renal replacement therapy (RRT) but access to RRT for children in low resource settings is limited. Our study explored the role of haemodialysis in the management of children with AKI in a low resource setting in terms of aetiology and outcomes. Methods: A review of patients managed in the Paediatric Nephrology Unit, University College Hospital Ibadan, South-West Nigeria, who underwent haemodialysis for AKI from January 2006 to December 2014. Results: Sixty-eight patients (55.9% males), aged 3–16 (mean ± standard deviation, 9.0 ± 3.4) years were studied. The causes of AKI were sepsis (22.1%), malaria (17.6%) and glomerulonephritis (17.6%), intravascular haemolysis—cause unknown (16.2%), G6PDH deficiency (7.4%), malignancy (8.8%) and haemoglobinopathy (5.9%). The number of sessions of haemodialysis ranged from 1 to 10 (mode = 2 sessions) over a period of 1–55 days. Mortality was 27.9% (n = 19) and was related to the aetiology of AKI (P = 0.000): no deaths among patients with intravascular haemolysis or malaria, six deaths among patients with sepsis (40%), six (50%) among the patients with glomerulonephritis, while all the patients with malignancies died. Conclusions: The outcome of haemodialysis for AKI in Nigeria is relatively good and is related to the underlying aetiology of AKI. In addition to peritoneal dialysis, intermittent haemodialysis may have a role in the management of paediatric AKI in low resource settings and should be supported.